2015
DOI: 10.18869/acadpub.jafm.67.223.22916
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Generation Analysis for Stagnation Point Flow in a Porous Medium over a Permeable Stretching Surface

Abstract: This paper presents entropy generation analysis for stagnation point flow in a porous medium over a permeable stretching surface with heat generation/absorption and convective boundary condition. We have used Von Karman transformations to transform the governing equations into ordinary differential equations.Thevelocity, temperature and concentration profiles obtained using the Homotopy Analysis Method. The HAM is a valid mathematical tool for most of non-linear problems in science and engineering. Finally we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…The SQLM has been used in a limited number of studies to solve boundary layer flow, heat and mass transfer problems [34]. The physical parameters in this paper are mostly chosen from the literature, for example in the papers [21,26,27,35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SQLM has been used in a limited number of studies to solve boundary layer flow, heat and mass transfer problems [34]. The physical parameters in this paper are mostly chosen from the literature, for example in the papers [21,26,27,35].…”
Section: Resultsmentioning
confidence: 99%
“…The successive linearization method (SLM) and Chebyshev spectral collocation method are used. Rashidi et al [21] studied entropy generation in nanofluid flow along a permeable stretching surface near the stagnation point with heat generation/absorption and a convective boundary condition. Bhatti et al [22] used the successive linearization method (SLM) to study the entropy generation on non-Newtonian Carreau nanofluid over a shrinking sheet.…”
Section: Introductionmentioning
confidence: 99%
“…In one statistical interpretation of entropy, it is found that for a very large system in thermodynamic equilibrium, entropy S is proportional to the natural logarithm of a quantity Ω corresponding to S and can be realized; that is, S " KlnΩ, in which K is related to molecular energy. On the other hand, entropy generation analysis [5][6][7][8][9][10][11] is used to optimize the thermal engineering devices for higher energy efficiency; it has attracted wide attention to its applications and rates in recent years. In order to access the best thermal design of systems, by minimizing the irreversibility, the second law of thermodynamics could be employed.…”
Section: Clausius's Entropymentioning
confidence: 99%
“…In such studies, monitoring the entropy generation is crucial in characterizing such systems . The entropy generation defines irreversibility and accounts for energy losses . As a consequence, by controlling entropy generation, the performance of engineering systems can be enhanced.…”
Section: Introductionmentioning
confidence: 99%